Humidity-Insensitive NO2 Sensors Based on SnO2/rGO Composites - Wang, Yingyi; Liu, Lin; Sun, Fuqin; Li, Tie; Zhang, Ting; Qin, Sujie (Frontiers in Chemistry, 2021)
This study reported a novel humidity-insensitive nitrogen dioxide (NO2) gas sensor based on tin dioxide (SnO2)/reduced graphene oxide (rGO) composites through the sol-gel method. The sensor demonstrated ppb-level NO2 detection in p-type sensing behaviors (13.6% response to 750 ppb). Because of the synergistic effect on SnO2/rGO p-n heterojunction, the sensing performance was greatly enhanced compared to that of bare rGO. The limit of detection (LOD) of sensors was as low as 6.7 ppb under dry air. Moreover, benefited from the formed superhydrophobic structure of the SnO2/rGO composites (contact angle: 149.0°), the humidity showed a negligible influence on the dynamic response (Sg) of the sensor to different concentration of NO2 when increasing the relative humidity (RH) from 0 to 70% at 116℃. The relative conductivity of the sensor to 83% RH was 0.11%. In addition, the response ratio (Sg/SRH) between 750 ppb NO2 and 83% RH was 649.0, indicating the negligible impaction of high-level ambient humidity on the sensor. The as-fabricated humidity-insensitive gas sensor can promise NO2 detection in real-world applications such as safety alarm, chemical engineering, and so on.